2016
DOI: 10.21873/anticanres.11224
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA snaR Regulates Proliferation, Migration and Invasion of Triple-negative Breast Cancer Cells

Abstract: LncRNA snaR was found to be up-regulated in breast cancer cells, and the cancer progression of MDA-MB-231 cells was significantly suppressed by down-regulation of snaR. Therefore, snaR knockdown has potential as a treatment modality for triple-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…Accumulated studies have shown the regulating role of lncRNAs in cell proliferation, metastasis, invasion and apoptosis (32,33). HAS1 has been regarded as a promising diagnostic biomarker or therapeutic target for various human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated studies have shown the regulating role of lncRNAs in cell proliferation, metastasis, invasion and apoptosis (32,33). HAS1 has been regarded as a promising diagnostic biomarker or therapeutic target for various human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved that altered expression of many lncRNAs are closely associated with the progression of BC. Downregulation of lncRNA snaR inhibits proliferation, migration, and invasion of BC cells and may be a potential treatment for triple-negative BC (12). lncRNA OR3A4 facilitates cell proliferation and cell migration in BC through inducing epithelial-mesenchymal transition (13).…”
Section: Discussionmentioning
confidence: 99%
“…Similar in breast cancer, several lncRNAs such as ANRIL or UCA1 and snaR were revealed as upregulated and strongly associated with tumor progression or poor prognosis in previous studies. 12,13,[26][27][28] However, as breast cancer is an extremely heterogenic disease, these knockdown processes may not result as identical based on tumor subtypes or characteristics. Therefore, the study of biological functions of lncRNA should be conducted differently according to the subtype of breast cancer.…”
Section: Discussionmentioning
confidence: 99%